EXPLORING THE INTEGRATION OF TRADITIONAL BATIK TECHNIQUES AND NANOTECHNOLOGIES IN CONTEMPORARY JEWELRY: PERSPECTIVES, INNOVATIONS - MATCAN-LISENCO, I. I. (Art and Design, 2024)
Purpose: The study explores the integration of traditional batik techniques into contemporary jewelry design, aiming to create innovative pieces that blend tradition with modernity. It aims to develop new techniques and materials, improve the accessibility and durability of batik jewelry, and promote cultural heritage. The research focuses on the application of technological innovations such as digital printing, nanotechnology, LED integration, augmented reality, and 3D printing to revolutionize jewelry design and bring significant aesthetic and functional improvements. Methodology. Various research methods are presented for studying the integration of batik into contemporary fashion accessories. These methods include historical research analyzing the tradition of batik and its evolution in the context of contemporary jewelry. Typological research classifies types of jewelry that incorporate batik elements and those that imitate batik. The author examines the design and techniques used in jewelry, including the combination of tradition and innovation through formal-stylistic analysis. The analysis of cultural and ethnic influences is also present, studying how batik reflects and promotes cultural heritage, adding a touch of authenticity and originality. Finally, the technological research method investigates technological innovations such as nanotechnology and 3D printing and their impact on jewelry design. Results. The study reveals multiple ways of integrating batik into contemporary jewelry, including batik inlays, elements that imitate batik, and the incorporation of batik fabrics into designs. A classification of types of jewelry with batik elements is provided, along with examples and possibilities for creative exploration. Different types of elements that imitate batik are also identified and categorized based on material and technique. Technological innovations such as digital printing, nanotechnology, LED integration, augmented reality, and 3D printing offer new possibilities for creating batik jewelry. Examples include using nanotechnology for fabric protection, LED integration for illuminated elements, and 3D printing for complex jewelry elements. The study discusses the advantages and disadvantages of these innovations, highlighting their potential to revolutionize contemporary jewelry design and improve its durability, aesthetics, and functionality. Additionally, combining nanotechnologies with batik in jewelry design opens opportunities for innovations such as smart jewelry with nanosensors, composite materials for durability, and enhanced dyeing processes for vibrant, fade-resistant colors. The discussions emphasize the importance of combining tradition with innovation in contemporary jewelry design and address the prospects and challenges of using batik and nanotechnologies in this field. Scientific novelty. The study demonstrates how integrating traditional batik techniques into contemporary jewelry design, combined with technological innovations such as nanotechnology, 3D printing, and augmented reality, can enhance the durability, aesthetics, and functionality of these jewelry pieces, thus opening new horizons in jewelry design. Practical significance. The practical novelty of this study lies in proposing concrete and applicable solutions for developing contemporary jewelry that integrates batik and nanotechnologies. By presenting specific examples of jewelry, the study provides inspiration and practical guidance for designers and manufacturers in the jewelry industry.